Factors affecting bioremedation of hydrocarbons in terrestrial environment - Mohajeri, L. (2006)
The success of oil spill bioremediation depends on our ability to establish and maintain conditions that favor enhanced oil biodegradation rates in the contaminated environment. Studies show that concentrations of available nitrogen and phosphorous are the main limiting factors. In addition, temperature and oxygen could be limiting as well. Most laboratory studies have focused on the potential of using nutrient amendments to enhance oil biodegradation. Studies have demonstrated that microbial population is rarely a limiting factor and nutrient addition alone had a greater effect on oil biodegradation than did the addition of microbial products. Available oxygen in the soils is quickly depleted through metabolism by aerobic organisms and chemical oxygen demand due to reduced chemical species. The weathering processes have effects on oil biodegradation. Weathering causes considerable changes in the chemical and physical properties of spilled oils. Other important factors affecting biodegradation of petroleum hydrocarbons include pH and salinity. Although many factors can affect oil biodegradation, not many environmental factors can be easily manipulated to enhance this process. For example, it is not practical to change wetland salinity, and nothing can be done to change the climate.